The origins of viruses: evolutionary dynamics of the escape hypothesis - O’Brien, John T.; George, Asha M.; Bonsall, Michael B. (Frontiers in Virology, 2025)
IntroductionSeveral hypotheses exist about how viruses first emerged on Earth. Understanding whether viruses escaped from cells, remained from devolved cells, or emerged before cells is key to comprehending the origins of viruses and life in general.MethodsHere, we analyze the evolutionary dynamics of the escape hypothesis (as proposed by Forterre and Krupovic) for viral origins. We developed theoretical and numerical approaches to investigate the dynamics of the virus escape hypothesis and highlighted which parameters (e.g., maturation rate, infected cell death rate, virus replication rate, infection rate) influence virus evolutionary origins and reinfection dynamics.ResultsCritically, we demonstrate that viral death rate (μV) and infected cell death rate (μI) must exceed a certain threshold for viruses to emerge and persist through the escape hypothesis. Furthermore, we demonstrate that unfaithful or unequal ribocell division is a necessary component of the escape hypothesis. We also examined early virus strategies for proliferation by comparing budding and lysing virus reproduction modes.DiscussionOur results highlight the importance of certain biological characteristics (e.g., maturation rate, infection rate, lysing rates, budding rates), required for the emergence of viruses via the escape hypothesis. The model we present here provides a sound basis for further work on the evolutionary dynamics of virus origins.